The Existence of Customary Criminal Sanctions from the Perspective of Living Law and the Reform of the National Criminal Code - Laia, Hepy Krisman (PT. Sinergi Legal Publisher, 2026)
This study examines the existence of customary criminal sanctions from a living law perspective and their relevance to the reform of the National Criminal Code. In Indonesia's pluralistic society, customary law is part of the living norms and is practically adhered to, including in the mechanism for imposing sanctions for violations. The existence of customary criminal sanctions not only has sociological legitimacy but also receives constitutional recognition as long as it does not conflict with the principles of the rule of law and human rights. The reform of the Criminal Code through Law Number 1 of 2023 opens up space for recognition of living law in society, thus demonstrating a paradigm shift from a positivistic approach to a more contextual and responsive approach to legal pluralism. This study uses normative legal methods with statutory and conceptual approaches, and is analyzed qualitatively through deductive reasoning. The results of the study indicate that the integration of customary criminal sanctions into the national criminal justice system must be designed proportionally, taking into account the principles of legality, legal certainty, and protection of human rights. An ideal normative design requires clear boundaries regarding the types of cases, a coordination mechanism between customary institutions and law enforcement officials, and a restorative justice approach as a bridge of harmonization. Thus, recognition of customary criminal sanctions is not only a form of respect for tradition, but also part of an effort to build national criminal law that is rooted in community values ​​and remains in line with constitutional principles.